Measuring the process and rate of exogenous DNA degradation during digestion in mice - Ruiqi Xing; Hui Liu; Xia Qi; Lingzi Pan (Scientific Reports, 2022)
Abstract This study aimed to perform qualitative and quantitative examination of DNA degradation during the digestion process in the mouse gut through PCR, qPCR and short tandem repeat (STR) analysis. Human blood leukocytes were gavaged into the digestive tract in mice. GAPDH, TH01, TPOX and D7S820 genes in the contents of the stomach and small intestine were analyzed with PCR and qPCR at various times pre- and post-gavage. Through STR analysis, 21 human genomic DNA loci were analyzed. The half-life of DNA degradation, and the relationship between the average peak area and digestion time were determined. The PCR results showed bands of amplified genes at pre-gavage (0 min) and post-gavage (40, 80 and 120 min) from the mouse stomach contents, whereas no DNA bands from small intestinal chyme were observed after gavage. The qPCR results revealed a significant decrease in DNA concentrations during 40–120 min in the mouse stomach after gavage. At 120 min, 85.62 ± 8.10% of the DNA was degraded, and the half-life of exogenous DNA degradation in the mouse stomach was 70.50 ± 5.46 min. At various digestion times, almost no target genes were detected in the mouse small intestinal chyme. STR analysis showed a decrease in allele numbers with bowel advancement in the small intestine in mice. The degradation of exogenous DNA was higher in the mouse stomach during the first 2 h, and almost complete degradation was observed within 40 min after entering the small intestine in mice.